BEYOND BUILDING CONDITION ASSESSMENT: THE INTEGRATED SCHOOL REVITALIZATION PRIORITIZATION ASSESSMENT INSTRUMENT (ISRPAI) - Paramitha Mega Putri; Fajar Sri Handayani; Ary Setyawan (RADJA PUBLIKA, 2026)
School revitalization programs are essential for ensuring the safety, functionality, and sustainability of educational infrastructure. However, existing school building assessment approaches primarily focus on physical building conditions and provide limited support for broader revitalization prioritization decisions. This study examines the current landscape of school infrastructure prioritization and school building assessment research and proposes an integrated assessment instrument for school revitalization prioritization. A literature review combined with bibliometric and thematic analyses was conducted using Scopus-indexed publications. Two datasets were analyzed: 108 articles related to school infrastructure prioritization and 46 articles related to school building assessment. Bibliometric mapping was performed using VOSviewer to identify dominant research themes, while thematic analysis was employed to synthesize assessment indicators and identify research gaps. The findings indicate that existing assessment approaches are predominantly oriented toward physical-condition indicators, including structural integrity, architectural deterioration, utility performance, and safety considerations. In contrast, educational demand, asset management, and regional context factors remain underrepresented despite their potential influence on revitalization priorities. Based on the identified gaps, this study proposes the Integrated School Revitalization Prioritization Assessment Instrument (ISRPAI), which comprises four dimensions: Building Condition, Educational Demand, Asset Management, and Regional Context. The instrument incorporates eleven indicators, including school capacity utilization, active classroom availability, land status, maintenance history, disaster vulnerability, accessibility, and socioeconomic conditions. The proposed ISRPAI extends conventional building condition assessment approaches by providing a more comprehensive basis for school revitalization prioritization and offers a conceptual foundation for future validation studies and decision-support systems in educational infrastructure planning.